2011
DOI: 10.1111/j.1468-3083.2011.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of interdigital erythrasma in southern region of Turkey

Abstract: Interdigital erythrasma is a commonly seen condition and can clinically mimic tinea pedis. A Wood's lamp is a good diagnostic tool, but Gram staining, particularly in those with a negative Wood's lamp result, may be a useful method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…Cases with erythrasma can be diagnosed by positive Wood's lamp examination and/or Gram staining/culture [ 28 ]. In the present study, positive coral red fluorescence with Wood's light, which is characteristic for erythrasma, was found in 24% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases with erythrasma can be diagnosed by positive Wood's lamp examination and/or Gram staining/culture [ 28 ]. In the present study, positive coral red fluorescence with Wood's light, which is characteristic for erythrasma, was found in 24% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Morales-Trujillo et al [ 5 ] examined 73 patients, of whom 24 (32.8%) were diagnosed with erythrasma. Inci et al [ 28 ] concluded that the rate of erythrasma was found to be 46.7% among 122 patients with interdigital foot lesions. Svejgaard et al [ 31 ] reported a prevalence of 51.3%, (prior to military service) and 77.1% (reexamined at the end of military service) in a group of Danish military recruits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in their study, found an increased prevalence of interdigital erythrasma among men. [ 15 ] In our study, the most common site of erythrasma was the axillary region (75%). One female patient presented with involvement of bilateral axillae, inframammary, cubital, and inguinal regions.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, findings of fungal infection were detected with KOH examination in 31.6% of these patients. If a Wood's light examination is negative, a Gram staining and bacterial culture should be performed (32).…”
Section: öZmentioning
confidence: 99%